2010
DOI: 10.1007/s10856-010-4083-8
|View full text |Cite
|
Sign up to set email alerts
|

The bio-functional role of calcium in mesoporous silica xerogels on the responses of osteoblasts in vitro

Abstract: Mesoporous silica xerogels with various amount of calcium (0, 5, 10 and 15%, named m-SXC0, m-SXC5, m-SXC10 and m-SXC15, respectively) were synthesized by template sol-gel methods, and cell responses to m-SXCs were studied using murine pre-osteoblast MC3T3-E1 in vitro. The results showed that cell morphology was not affected by m-SXCs indicating good biocompatibility. Furthermore, cell proliferation ratio on the m-SXCs increased over time, among which m-SXC10 was highest. NO production obviously rose with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…While many in vitro studies have demonstrated the proper ionic doses favorable for cell proliferation and osteogenesis, a limited number of studies have examined the functions in 3D scaffolds. Different Ca concentrations incorporated into a collagen gel showed that low concentrations (2-4 mM) promoted osteoblast proliferation, medium concentrations (6-8 mM) induced cellular differentiation and mineralization, whereas concentrations greater than 8 mM induced cytotoxicity [154]. On the other hand, high Ca content incorporated within silica based microspheres showed enhanced cell proliferation [155], while the increased Ca level was shown to be related with lower levels of ALP activity [151].…”
Section: Control Of Therapeutic Ionsmentioning
confidence: 99%
“…While many in vitro studies have demonstrated the proper ionic doses favorable for cell proliferation and osteogenesis, a limited number of studies have examined the functions in 3D scaffolds. Different Ca concentrations incorporated into a collagen gel showed that low concentrations (2-4 mM) promoted osteoblast proliferation, medium concentrations (6-8 mM) induced cellular differentiation and mineralization, whereas concentrations greater than 8 mM induced cytotoxicity [154]. On the other hand, high Ca content incorporated within silica based microspheres showed enhanced cell proliferation [155], while the increased Ca level was shown to be related with lower levels of ALP activity [151].…”
Section: Control Of Therapeutic Ionsmentioning
confidence: 99%
“…There have been many reports of enhanced cellular bioactivity using biosilicates (P 2 O 5 -Na 2 O-CaOSiO 2 ), 1 calcium-magnesium-silicate ceramics, 2 calcium-silica ceramics, 3 and bioactive glass (Ca-Sr-Na-Zn-Si). 4 Mesoporous silica particles are also being used for controlled release scaffolds, 5 and many bioceramics include a silica component.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A mixture of silicon and calcium, 3,11 or mixtures with various other materials, including zinc and magnesium, 12 improve both gene expression and biological performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ionic dissolution products containing Ca and Si from materials can stimulate osteoblast proliferation and gene expression [39]. Previously Hench et al showed that approximately 17-21 ppm of soluble Si and 60-88 ppm of soluble Ca ions were required for osteoblasts to grow, differentiate and form a mineralized extracellular matrix and create bone nodules [40].…”
Section: Figurementioning
confidence: 99%